2020
DOI: 10.1186/s13567-020-00862-1
|View full text |Cite
|
Sign up to set email alerts
|

Serotyping and pathotyping of Glaesserella parasuis isolated 2012–2019 in Germany comparing different PCR-based methods

Abstract: Glaesserella parasuis is an important pathogen in swine production. It acts as a primary pathogen in systemic Glässer´s disease and as a secondary pathogen in Porcine Respiratory Disease Complex. In this study, a collection of 308 isolates from carrier animals and individuals with respiratory or Glässer´s disease isolated 2012–2019 in Germany was analysed. Isolates were characterized for serovar implementing two different PCR methods. Additionally, two different PCR methods for pathotyping isolates were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 35 publications
7
28
0
Order By: Relevance
“…In the present study, most internal isolates were identified as virulent by LS-PCR, while most nasal isolates were non-virulent. Our results agree with previous reports [ 25 , 28 , 39 41 ] and supported our disease association observations for serovar 7 isolates. In our study, most serovar 7 (75/77, 97.4%) strains were internal and classified as virulent by the LS-PCR.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In the present study, most internal isolates were identified as virulent by LS-PCR, while most nasal isolates were non-virulent. Our results agree with previous reports [ 25 , 28 , 39 41 ] and supported our disease association observations for serovar 7 isolates. In our study, most serovar 7 (75/77, 97.4%) strains were internal and classified as virulent by the LS-PCR.…”
Section: Discussionsupporting
confidence: 94%
“…The serovars' overall distribution varied slightly among countries, and four serovars (1, 4, 5/12, and 7) accounted for half of all isolates. Serovars 4 and 5/12, in particular, were consistently represented across all regions in this study and previous studies [13,[22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations